A Numerical Model for the Temperature Regime of a Concrete Gravity Dam in the Climatic Conditions of Northern Vietnam. Issue 1 (July 2020) - Aniskin, N; Nguyen, T
Abstract: One of the main impacts on concrete gravity dams is the temperature factor. The effect of temperature factor on concrete dams will create additional deformation and stress, which can lead to tensile stresses and so gives rise to the thermal cracking. So, forecasting the thermal regime and thermal stress state in concrete gravity dams is a difficult task because taking into account a large number of influencing factors. This paper presents numerical modeling results on the temperature regime of the Banmong (Son La Province, Vietnam) concrete gravity dam with a height of 45m. The model has created by the MIDAS software package and can assess the influence of temperature factors on the dam structure during construction and operation period. The results obtained may be used when designing and making appropriate recommendations.